A case study of strategies for intentionally building course community to support diverse learners in an introductory statistics course. (21st March 2022) - Taylor, Laura L.; Doehler, Kirsten; VanKrevelen, Ryne; Weaver, Mark A.; Trocki, Aaron D.
Abstract: This article presents a multi‐part initiative to support diverse learners by building class community and peer networks in an introductory statistics course. This was accomplished through multiple techniques, such as implementing icebreaker questions and using randomly assigned student working groups. The Socrative online software utilized regularly by instructors allowed students to be randomized into groups to collaboratively answer questions provided by the instructors. A multi‐part group project was also administered where students worked cooperatively to analyze swim race data from the 2016 Olympics. Students completed a pre‐semester survey in which they provided feedback on previous mathematics or statistics courses related to the level of course engagement, the benefit of group learning, and their ability to discuss course content during class. A post‐semester survey was administered to answer similar questions regarding the statistics course they were currently taking.